Purificação e caracterização química e funcional de uma lectina tipo-C ligante de D-galactose da peçonha de Bothropoides pauloensis (Bothrops pauloensis) - Castanheira, Letícia Eulálio (2011)
CHAPTER II: C-type lectins are carbohydrate binding-proteins, which have been described in many organisms, including snake venoms. In the present work, we demonstrate the isolation and biochemical characterization of a C-type lectin from Bothropoides pauloensis venom. The protein named BpLec is D-galactose specific and agglutinates erythrocytes of blood from dog and cat. BpLec was also shown to be stable in any pH range of 2-11 and in the presence of some cationic ions, although its haemmaglutinating activity was abolished at temperatures above 50 °C. BpLec is homodimeric, exhibiting two chains of relative molecular mass of 16.8 kDa each, as estimated by MALDI TOF analysis. The acid protein presents an isoeletric point of 5.36. The primary structure of 132 amino acids for each subunit of BpLec, determined by Edman degradation, revealed a high identity (between 95% and 86%) when compared with the sequences of other related proteins. Regarding to pharmacological applications, the protein was effective in inhibiting Gram-positive bacteria, but not Gram-negative bacteria. In addition, BpLec was a potent agglutinating factor of promastigote forms of Leishmania (Leishmania) amazonensis. This data suggests an interaction between BpLec and galactose present in parasite surface, which could alter some biological functions from the parasite.